2020
DOI: 10.1111/jgs.16967
|View full text |Cite
|
Sign up to set email alerts
|

Home‐Based Medical Care: High‐Value Health Care During Coronavirus Disease 2019 and Beyond

Abstract: is a 78-year-old woman with a history of congestive heart failure, chronic obstructive pulmonary disease, and recent stroke who was discharged 1 month ago from a subacute rehabilitation facility. She moved in with her son because she now requires a walker and cannot return to her third-floor apartment. One evening, Ms. H develops a lowgrade fever and mild shortness of breath intermittently relieved by her albuterol inhaler. Her son is worried, but knows that his mom does not want to return to the hospital.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 22 publications
0
8
0
Order By: Relevance
“…Indeed, recent literature advocates for a more integrated role for home-based medical care. 13 , 14 The expansion of telemedicine may allow some HBPC clinicians to increase patient panels by reducing travel time to and between visits. Collaborations with health systems and health departments increased, fostering better access to supplies and workforce and targeted outreach to at-risk groups.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, recent literature advocates for a more integrated role for home-based medical care. 13 , 14 The expansion of telemedicine may allow some HBPC clinicians to increase patient panels by reducing travel time to and between visits. Collaborations with health systems and health departments increased, fostering better access to supplies and workforce and targeted outreach to at-risk groups.…”
Section: Discussionmentioning
confidence: 99%
“…Video‐based telehealth has emerged as an important care‐delivery innovation within HBPC, especially during the COVID‐19 pandemic. Not only does telehealth reduce costs, transportation, and time on the part of the patient, but the pandemic also has highlighted additional benefits such as reduced infection exposures 6,7 . The federal government has recognized these benefits and implemented regulatory waivers and rule changes aimed at increasing telehealth accessibility, facilitating its rapid uptake since early 2020 8‐11 …”
Section: Introductionmentioning
confidence: 99%
“…The COVID-19 pandemic led to the prioritization of hospitalization for severely ill patients both in Japan and overseas, whereas those with mild illnesses were increasingly treated at home; the home medical and nursing care system was strengthened to support this transition. [27][28][29] Therefore, it is now easier to provide acute treatment at home than when this study was carried out. Furthermore, it has been reported that 55% of older patients in Japan hospitalized with COVID-19 infection developed functional decline.…”
Section: Discussionmentioning
confidence: 99%
“…We consider the possibility that home care might currently have an equal or even better prognosis than before the pandemic. The COVID‐19 pandemic led to the prioritization of hospitalization for severely ill patients both in Japan and overseas, whereas those with mild illnesses were increasingly treated at home; the home medical and nursing care system was strengthened to support this transition 27–29 . Therefore, it is now easier to provide acute treatment at home than when this study was carried out.…”
Section: Discussionmentioning
confidence: 99%